2005
DOI: 10.1148/radiol.2372041429
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Shoulder Instability: Accuracy of MR Arthrography in the Classification of Anteroinferior Labroligamentous Injuries

Abstract: MR arthrography is accurate in enabling classification of acute and chronic anteroinferior labroligamentous injuries, although correct interpretation of Perthes lesions remains difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 29 publications
4
111
1
5
Order By: Relevance
“…In our patients, MRA demonstrated the highest sensitivity at 94.4% among the groups in detecting Bankart lesions, which is similar to the results of studies (15)(16)(17), which advocate MRA as the gold standard for diagnosing anterior-inferior labral lesions. The advantages of MRA over other forms of imaging are the ability to detect subtle lesions of the intra-articular structures such as the labrum and ligaments (18).…”
Section: Discussionsupporting
confidence: 89%
“…In our patients, MRA demonstrated the highest sensitivity at 94.4% among the groups in detecting Bankart lesions, which is similar to the results of studies (15)(16)(17), which advocate MRA as the gold standard for diagnosing anterior-inferior labral lesions. The advantages of MRA over other forms of imaging are the ability to detect subtle lesions of the intra-articular structures such as the labrum and ligaments (18).…”
Section: Discussionsupporting
confidence: 89%
“…Sensitivity and specificity values of the MRa were 89-96% and 84-89%, respectively. These results are consistent with the results of a previously published study of Waldt et al [8], evaluating 205 conventional MR arthrograms with arthroscopy as reference standard.…”
Section: Discussionsupporting
confidence: 92%
“…Direct magnetic resonance (MR) arthrography is considered to be the most accurate imaging technique for visualisation of the anteroinferior labroligamentous complex because of optimal joint distention with a diluted mixture of Gd-DTPA and superb soft tissue contrast [3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Studies evaluating specific labral regions have reported sensitivities for superior and superior labrum anterior-posterior (SLAP) tears ranging from 50 to 100% [11][12][13][14][15]. Anteroinferior labral tears have been reported with a sensitivity of 88% [16], anterior tears 86-95% [11], and posterior tears 7.7%.…”
Section: Discussionmentioning
confidence: 99%